Decidualized ovarian endometrioma mimicking malignancy in pregnancy: a case report and literature review - Min Yin; Tao Wang; Sijian Li; Xinyue Zhang; Jiaxin Yang (Journal of Ovarian Research, 2022)
Abstract Background Ovarian endometrioma is a common gynecologic disease among reproductive-aged women. Pregnancy-related hormonal status may lead to changes of decidualization, which may resemble ovarian malignancies in sonographic appearance. Here we present a case of decidualized ovarian endometrioma clinically mimicking malignant transformation. Case presentation A 37-year-old pregnant woman presented to our hospital at 25 + 5 weeks of gestation with a persistent left adnexal mass that was first detected on routine ultrasound in the first trimester. Transvaginal and transabdominal ultrasound showed a cystic mass of size 8.4 × 5.8 cm in the left ovary with abundant blood flow signals in the papillary medium echo of the capsule wall and inner wall, raising concern for malignant ovarian tumor. After a multidisciplinary discussion, the patient underwent laparoscopic left salpingo-oophorectomy. The results of the frozen section revealed decidualized endometrioma and the final histopathology confirmed endometrioma with extensive decidualization. The patient’s postoperative recovery was uneventful and she was discharged on the 4th postoperative day. Conclusions Decidualized ovarian endometrioma is rare. Sonography and magnetic resonance imaging are helpful for differential diagnosis. Conservative management of expectant management and serial monitoring should be adopted if decidualized endometriosis is suspected.